2020
DOI: 10.1182/bloodadvances.2020002064
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy and autologous stem cell transplant in elderly patients with primary CNS lymphoma: a pilot study

Abstract: Key Points Age-adapted high-dose chemotherapy and autologous stem cell transplantation is safe and highly effective in elderly patients with PCNSL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…Only recently was this method of consolidation prospectively explored in a population that included patients >70 years of age. Schorb et al reported that HDC-ASCT with busulfan/thiotepa conditioning was feasible and well tolerated in a carefully selected group of fourteen patients with a median age of 74 (range, 69–79) with no treatment related deaths ( 49 ). However only 40% of screened patients met eligibility for enrollment, highlighting the fact that there is a subset of patients, predominantly the elderly, for whom HDC-ASCT is not an option and whom are high risk for neurotoxicity with WBRT.…”
Section: Consolidation Therapymentioning
confidence: 99%
“…Only recently was this method of consolidation prospectively explored in a population that included patients >70 years of age. Schorb et al reported that HDC-ASCT with busulfan/thiotepa conditioning was feasible and well tolerated in a carefully selected group of fourteen patients with a median age of 74 (range, 69–79) with no treatment related deaths ( 49 ). However only 40% of screened patients met eligibility for enrollment, highlighting the fact that there is a subset of patients, predominantly the elderly, for whom HDC-ASCT is not an option and whom are high risk for neurotoxicity with WBRT.…”
Section: Consolidation Therapymentioning
confidence: 99%
“…The studies were published between 1992 and 2020. Only eight out of 26 studies were specifically designed for elderly patients with an age cut-off of 60 years or older [31,[55][56][57][58][59][60][61]. The remaining studies included patients with a wider age range and also provided individual patient data or subgroup data for elderly patients.…”
Section: Key Characteristics Of Prospective Non-randomized Studiesmentioning
confidence: 99%
“…Nevertheless, this approach is still very scarce. In a pilot study, Schorb et al have utilized the Cumulative Illness Rating Scale–Geriatric score as an inclusion criterion in addition to age [ 24 ]. Such approaches should be developed.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…In randomized trials, this strategy has been shown to be an alternative option to WBRT as consolidation, with a better preservation of neurocognitive functions at least in the short-term follow-up, but at the price of an expected important systemic toxicity and a toxic death rate of 5–10%. While this strategy has been classically reserved for younger patients, a few recent studies have supported its use in selected older patients with age-adapted protocols [ 24 , 59 , 82 ].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation